1992
DOI: 10.1002/mrd.1080330111
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of caltrin proteins from seminal vesicle of the guinea pig

Abstract: Caltrin proteins from seminal vesicle content of the guinea pig bind with great specificity to different regions of the spermatozoa. Indirect immunofluorescence studies with polyclonal antibodies showed that caltrin I binds to the head, on the acrosomal cup, while caltrin II binds on the principal tail and the neck. No fluorescence was detected either in the midpiece or in the post-acrosomal area of the head when sperm were exposed to either of the caltrins. Calcium-induced hyaluronidase release, which occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
70
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 24 publications
6
70
0
Order By: Relevance
“…Closely related proteins have been cloned from epididymal tissue of other species (Ellerbrock et al, 1994;Xu et al, 1996). The positions of half-cysteines suggested that they are twodomain members of the 'four-disulfide core'-or 'whey acidic' protein (WAP)-domain proteins, to which the human seminal plasma proteinase inhibitor, HUSI-I/SLPI (Seemüller et al, 1986;Jin et al, 1997), and a decapacitation factor of guinea-pig spermatozoa, caltrin II, belong (Coronel and Lardy, 1992). HE4 antipeptide antisera react with an antigen of the epididymal epithelium and duct lumen (Fig.…”
Section: Putative Secretory Proteinase Inhibitorsmentioning
confidence: 99%
“…Closely related proteins have been cloned from epididymal tissue of other species (Ellerbrock et al, 1994;Xu et al, 1996). The positions of half-cysteines suggested that they are twodomain members of the 'four-disulfide core'-or 'whey acidic' protein (WAP)-domain proteins, to which the human seminal plasma proteinase inhibitor, HUSI-I/SLPI (Seemüller et al, 1986;Jin et al, 1997), and a decapacitation factor of guinea-pig spermatozoa, caltrin II, belong (Coronel and Lardy, 1992). HE4 antipeptide antisera react with an antigen of the epididymal epithelium and duct lumen (Fig.…”
Section: Putative Secretory Proteinase Inhibitorsmentioning
confidence: 99%
“…They are small (M, = 5082 and 6255), basic (PIS 9.5 and 10.2) molecules that contain cysteines and carbohydrates in their structures [6]. Both caltrins inhibit with almost the same intensity the uptake of extracellular Ca2+ by capacitated epididymal spermatozoa [5].…”
mentioning
confidence: 99%
“…They are small (M, = 5082 and 6255), basic (PIS 9.5 and 10.2) molecules that contain cysteines and carbohydrates in their structures [6]. Both caltrins inhibit with almost the same intensity the uptake of extracellular Ca2+ by capacitated epididymal spermatozoa [5]. However, each caltrin interacts specifically with different zones of the spermatozoa and affects the development of Ca-dependent physiologic processes localized in those areas and involved in fertilization.…”
mentioning
confidence: 99%
See 2 more Smart Citations